NTRK gene fusions are detected in both secretory and non‐secretory breast cancers. Issue 3 (31st January 2022) - Maund, Sophia L.; Sokol, Ethan S.; Ang Houle, Armande; Ross, Jeffrey S.; Wilson, Timothy R.
Abstract: NTRK fusions represent a new biomarker‐defined population that can be treated with TRK inhibitors. Although rare, NTRK fusions are detected across a wide range of solid tumors. Previous reports suggest that NTRK fusions are limited to the secretory subtype of breast cancer. Here we examined NTRK fusions in a large real world next‐generation sequencing (NGS) dataset and confirmed secretory versus non‐secretory status using H&E images. Of 23 NTRK fusion‐positive cases, 11 were classified as secretory, 11 as non‐secretory, and one as mixed status. The secretory subtype trended younger, was predominantly estrogen receptor (ER)–, had lower tumor mutational burden, and exhibited lower levels of genomic loss of heterozygosity. The non‐secretory subtype was enriched for TP53 mutations. The secretory subtype was enriched for ETV6‐NTRK3 fusions in 7 of 11 cases, and the non‐secretory subtype had NTRK1 fusions in 7 of 11 cases, each with a different fusion partner. Our data suggests NTRK fusions are present in both secretory and non‐secretory subtypes, and that comprehensive genomic profiling should be considered across all clinically advanced breast cancers to identify patients that could receive benefit from TRK inhibitors.